Admission Blood Pressure in Relation to Clinical Outcomes and Successful Reperfusion After Endovascular Stroke Treatment. Issue 11 (November 2020) - van den Berg, Sophie A.; Uniken Venema, Simone M.; Mulder, Maxim J.H.L.; Treurniet, Kilian M.; Samuels, Noor; Lingsma, Hester F.; Goldhoorn, Robert-Jan B.; Jansen, Ivo G.H.; Coutinho, Jonathan M.; Roozenbeek, Bob; Dippel, Diederik W.J.; Roos, Yvo B.W.E.M.; et al.
Abstract : Background and Purpose: Optimal blood pressure (BP) targets before endovascular treatment (EVT) for acute ischemic stroke are unknown. We aimed to assess the relation between admission BP and clinical outcomes and successful reperfusion after EVT. Methods: We used data from the MR CLEAN (Multicenter Randomized Controlled Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands) Registry, an observational, prospective, nationwide cohort study of patients with ischemic stroke treated with EVT in routine clinical practice in the Netherlands. Baseline systolic BP (SBP) and diastolic BP (DBP) were recorded on admission. The primary outcome was the score on the modified Rankin Scale at 90 days. Secondary outcomes included successful reperfusion (extended Thrombolysis in Cerebral Infarction score 2B-3), symptomatic intracranial hemorrhage, and 90-day mortality. Multivariable logistic and linear regression were used to assess the associations of SBP and DBP with outcomes. The relations between BPs and outcomes were tested for nonlinearity. Parameter estimates were calculated per 10 mm Hg increase or decrease in BP. Results: We included 3180 patients treated with EVT between March 2014 and November 2017. The relations between admission SBP and DBP with 90-day modified Rankin Scale scores and mortality were J-shaped, with inflection points around 150 and 81 mm Hg, respectively. An increase in SBP above 150 mm Hg was associated with poor functional outcome (adjusted common odds ratio, 1.09 [95% CI, 1.04–1.15]) and mortality at 90 days (adjusted odds ratio, 1.09 [95% CI, 1.03–1.16]). Following linear relationships, higher SBP was associated with a lower probability of successful reperfusion (adjusted odds ratio, 0.97 [95% CI, 0.94–0.99]) and with the occurrence of symptomatic intracranial hemorrhage (adjusted odds ratio, 1.06 [95% CI, 0.99–1.13]). Results for DBP were largely similar. Conclusions: In patients with acute ischemic stroke treated with EVT, higher admission BP is associated with lower probability of successful reperfusion and with poor clinical outcomes. Further research is needed to investigate whether these patients benefit from BP reduction before EVT. Abstract : Supplemental Digital Content is available in the text.